2022
DOI: 10.1136/heartjnl-2022-321114
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and drivers of inappropriate dosing of non-vitamin K antagonist oral anticoagulants (NOACs) in patients with atrial fibrillation: a systematic review and meta-analysis

Abstract: ObjectiveThere has been limited systematic evaluation of outcomes and drivers of inappropriate non-vitamin K antagonist oral anticoagulants (NOACs) dosing among patients with atrial fibrillation (AF). This review identified and systematically evaluated literature on clinical and economic outcomes of inappropriate NOAC dosing and associated patient characteristics.MethodsMEDLINE, Embase, Cochrane Library, International Pharmaceutical Abstracts, Econlit, PubMed and NHS EEDs databases were searched for English la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…In a recent meta-analysis, Caso et al compared OLRD to on-label dosing (ie, both on-label reduced and on-label non-reduced). This showed that OLRD increased the risk of all-cause mortality (HR 1.28 (95% CI 1.10 to 1.49)) with a null effect on major bleeding (HR 1.04 (95% CI 0.90 to 1.19)) 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis, Caso et al compared OLRD to on-label dosing (ie, both on-label reduced and on-label non-reduced). This showed that OLRD increased the risk of all-cause mortality (HR 1.28 (95% CI 1.10 to 1.49)) with a null effect on major bleeding (HR 1.04 (95% CI 0.90 to 1.19)) 18…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews have evaluated the clinical consequences of such OLRD 14 16–18. However, the included studies in these reviews are highly heterogeneous, suffer from confounding and/or compare patients with OLRD to all patients receiving an on-label dose (ie, both on-label reduced and on-label non-reduced).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of underdosing of NOACs is global, and it might be explained by the fact that prescribers believe this might decrease the risk of bleeding without paying attention to the risk of ischemic stroke and all-cause mortality due to underdosing. [10,17,18] A single-center retrospective cohort study conducted in a teaching hospital in the Netherlands to evaluate the appropriateness of NOACs dosing in 3231 hospitalized patients with NVAF found that patients who were prescribed dabigatran, rivaroxaban, or apixaban received the reduced dose inappropriately in 5.4% compared to 4.5% who received overdose. [9] Additionally, another single-center retrospective cohort study in Japan included 316 patients to investigate NOACs appropriateness in NVAF patients revealed that patients who were prescribed dabigatran, rivaroxaban, apixaban, or edoxaban received the reduced dose inappropriately in 19.3% compared to only 2.5% received overdose.…”
Section: Tablementioning
confidence: 99%
“…A recent meta-analysis found that an overdose of NOACs can increase the risk of major bleeding, while an underdose can increase the risk of allcause mortality with no effect on ischemic stroke. [10] Rivaroxaban, is factor Xa inhibitor, has been approved to decrease the risk of stroke and systemic embolism in NVAF at a dose of 20 mg orally once daily in patients with a creatinine clearance (CrCl) >50 mL/min, and a dose of 15 mg orally once daily in patients with a CrCl ≤ 50 mL/min. The package insert of rivaroxaban recommends avoiding concomitant administration of known combined p-glycoprotein (P-gp) and strong CYP3A4 inhibitors such as ketoconazole, itraconazole, and ritonavir.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation